PENINGKATAN LITERASI AI DAN EFISIENSI ADMINISTRASI GURU MELALUI MODEL POWERPROMPT GURU DI SMAN 1 SUSUKAN - Saefurrohman Saefurrohman; R Soelistijadi; Dwi Budi Santosa; Rina Candra Noor S; Felix Andreas Sutanto (Intimas, 2026)
This community service program aims to improve teachers’ skills in utilizing artificial intelligence through prompt engineering at SMAN 1 Susukan, Semarang Regency. The activity was motivated by the high administrative workload and the inconsistent quality of teaching materials in implementing the Merdeka Curriculum. The Powerprompt Guru training emphasized hands-on practice in designing effective prompts using ChatGPT, enabling teachers to produce learning artifacts and school documents more quickly and consistently. A participatory co-creation approach was applied, involving teachers actively from needs analysis to artifact design and quality validation through an internal quality gate mechanism. The results indicated a 35 percent increase in teachers’ competencies based on pre-test and post-test comparisons. Approximately 91 percent of learning artifacts and all administrative documents were approved for upload to the school’s digital repository. The participant satisfaction survey recorded an average score of 4.6 out of 5, reflecting a highly positive response to the training and the digital system’s usefulness. The program fostered a culture of collaboration and sustainable digital documentation, enhancing teachers’ work efficiency. This prompt engineering-based training model has strong potential for replication in other schools with similar contexts and infrastructures.